2019
DOI: 10.1111/apa.15018
|View full text |Cite
|
Sign up to set email alerts
|

No effect of a musical intervention on stress response to venepuncture in a neonatal population

Abstract: Aim To investigate the effect of a musical intervention on neonatal stress response to venepuncture as measured by salivary cortisol levels and pain profile scores. Methods In a randomised control crossover trial, participants were randomised to both a control arm (sucrose) and intervention arm (sucrose and music) for routine venepuncture procedures. Salivary swabs were collected at baseline, 20 minutes post‐venepuncture and 4 hours post‐venepuncture. Pain levels were assessed using the Premature Infant Pain P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Discrepancies were resolved by discussion and consensus. The overall results showed that 27 RCTs had a low (69.2%), 17‐43 7 had a moderate (17.9%) 44‐50 and 5 had a high (12.8%) risk of bias 51‐55 …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Discrepancies were resolved by discussion and consensus. The overall results showed that 27 RCTs had a low (69.2%), 17‐43 7 had a moderate (17.9%) 44‐50 and 5 had a high (12.8%) risk of bias 51‐55 …”
Section: Resultsmentioning
confidence: 98%
“…Regarding the type of music selected (Table 1 and Table 2), the majority of studies ( n = 26, 66.7%) used lullaby‐style interventions (soothing sounds; repetitive patterns of rhythm; and slower pitch and tempo, with only vocal, musical instruments or both), 17‐22,24,26,30‐33,35,37,39,40,42,43,45,46,50‐55 such as Brahms lullaby ( n = 5, 12.82%) 17,18,22,31,39 and cultural lullabies (specific to the country or language) ( n = 8, 20.51%) 22,26,28,31,32,37,40,51 23,44,47‐49 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations